Preparation of high-strength polyimide membranes capped by ionic liquids. (June 2021) - Jiang, Pengfei; Jia, Hongge; Xu, Jingyu; Zhou, Hailiang; Zhang, Mingyu; Xu, Shuangping; Zang, Yu; Zhang, Xunhai; Zhang, Yuyan
In this study, we firstly used 1-carboxyethyl-3-methylimidazolium ionic liquid as a capping agent to terminate a binary linear polyimide containing different groups such as ether bonds, carbonyl groups, and fluorine, and prepared six kinds of polyimides capped with ionic liquids (IL-PI). The mechanical properties of the polyimide membranes capped with ionic liquids were higher than those of the uncapped polyimide membranes. The elastic modulus of polyimide membrane from 1, 3-bis (4-aminophenoxy) benzene (BPDA) and 3, 3′4, 4′-benzophenone tetracarboxydianhydride (BTDA) by using ionic liquid as the end capping agent (IL-BPDA-BTDA) was 2012 MPa, which is about 70 times higher than that without the end capping agent. In a TG test, all polyimides capped by ionic liquids showed good thermal properties. The residual amount of the polyimides was more than 40% at 1000 °C, which was higher than the other uncapped polyimides. In conclusion, polyimide membranes with high temperature resistance and high mechanical strength were prepared through an ionic liquid termination method.